Regional Capabilities, Transfers And Wide Of Area Influence To Capital Expenditures With Moderation Of Economic Growth - Pancawati Hardiningsih; Rachmawati Meita Oktaviani; Caecilia Srimindarti (The Indonesian Journal of Accounting Research, 2018)
Abstract: The proper allocation of capital expenditure will support the smoothness of government tasks and public facilities so that it will increase the productivity of the regional economy and job creation. This study aims to determine the effect of local revenues, general allocation funds, surplus funding budget and the area of the capital expenditure with the moderation of economic growth. The population in this research is the district/city of Central Java province in 2012-2014 as many as 35 consisting of 29 districts and six municipalities. Research data were analyzed by using multiple linear regression analysis of quasi model with a base of interaction. The results of hypothesis testing can be concluded that the local revenue affects the capital expenditure with negative intensity. While general allocation fund, economic growth, and size of the region have a positive effect on capital expenditure. However, the surplus funding budget has no impact on capital expenditure. Economic growth can be moderated by the effects of local revenues and general allocation funds on capital expenditures. While economic growth does not moderate the influence of surplus funding budget on capital expenditures. The result of this research can be used as policy and correction of decision for the central government in determining fund allocation, and it is hoped that local government will be more selective in the use of fund as well as to develop the potential of a regional economic sector to increase local revenue to be more independent.Abstrak:Alokasi belanja modal yang tepat akan mendukung kelancaran tugas pemerintah dan fasilitas publik sehingga akan meningkatkan produktivitas ekonomi daerah dan penciptaan lapangan kerja. Penelitian ini bertujuan untuk mengetahui pengaruh pendapatan lokal, dana alokasi umum, anggaran dana surplus dan luas belanja modal dengan moderasi pertumbuhan ekonomi. Populasi dalam penelitian ini adalah kabupaten / kota provinsi Jawa Tengah pada tahun 2012-2014 sebanyak 35 yang terdiri dari 29 kabupaten dan 6 kotamadya. Data penelitian dianalisis dengan menggunakan analisis regresi linier berganda model kuasi dengan basis interaksi. Hasil pengujian hipotesis dapat disimpulkan bahwa pendapatan lokal mempengaruhi belanja modal dengan intensitas negatif. Sedangkan dana alokasi umum, pertumbuhan ekonomi dan luas wilayah berpengaruh positif terhadap belanja modal. Namun, anggaran dana surplus tidak berpengaruh pada belanja modal. Pertumbuhan ekonomi dapat dimoderasi efek pendapatan lokal dan dana alokasi umum pada belanja modal. Sementara pertumbuhan ekonomi tidak memoderasi pengaruh anggaran dana surplus pada belanja modal. Hasil penelitian ini dapat digunakan sebagai kebijakan dan koreksi keputusan bagi pemerintah pusat dalam menentukan alokasi dana dan diharapkan pemerintah daerah akan lebih selektif dalam penggunaan dana serta untuk mengembangkan potensi sektor ekonomi daerah untuk meningkatkan pendapatan menjadi lebih mandiri.